Façonner une identité enseignante pour ne pas décrocher professionnellement et soutenir la réussite des élèves - Philippe Zimmermann (Université de Provence, 2016)
The link between the professional integrating/dropping process of teachers and student achievement appears as salient when looking at new teachers. Faced with students' learning difficulties, their professional identity is upset, to the point for many of them to gradually to leave the profession. A qualitative approach anchored on the assumptions and methodology of clinical activity (Clot, 2008) conducted with ten novice teachers from primary school, has highlighted the importance of collective work that of mutual recognition teacher - students, and the contrasting effects of alternation in teacher training. We discuss the hypothesis of a link between the professional process of dropping out and student success, pointing the necessity to be efficient, to renormalize prescriptions and a mutual recognition for a co-constructed (teacher and student) meaning given to their work. Prospects allow to question the favorable circumstances to integrate starting the first assignments, and recent training devices in academic centers encourage support for novice teachers.